The Evolution of Out‐of‐Hospital Medical Costs to and through Retirement1. Issue 1 (15th September 2016) - Johar, Meliyanni
Abstract : This paper shows how the cost of out‐of‐hospital medical services and prescription drugs change as Australians enter and live through retirement. We use a sample of over 65, 000 retired individuals aged forty‐five and over, and extract their Medicare claims for period 2005–2014. Analysing the expenditure distribution for up to eight years after retirement, the result shows that expenditure on medical services continues to increase while pharmaceutical expenditure declines for most retirees. Partially retired individuals have higher medical service cost but lower pharmaceutical cost, while those retiring prior to Age Pension age have slower growth in medical service and pharmaceutical costs.